Pastoral constitution on the church in the modern world. A re-reading fifty yeasr later - Camacho, SJ, Ildefonso (Razón y fe, 2018)
While Vatican II is seen, as experts say, as a development capable to renew the Church and place it in front of the world, constitution Gaudium et Spes (1965) is more in the line of the insight of John XXIII, right when he called the Council, and in the insight of Paul VI when it was taking place. To place the Church in the midst of the world and to inspire the evangelizing message, Gaudium et Spes reinforces the identity of human beings and everything human with the person and the mission of Christ. He invites anyone who believes in Him to live for and achieve a foretaste of Kingdom of God in our historical experience.
Keywords: developments; world; Paul VI; sign of the times; pastoral constitution; mission; integral development in solidarity